The Menstrual Cycle, Sex Hormones, and Anterior Cruciate Ligament Injury - Slauterbeck, James R. (National Athletic Trainers Association, 2002)
Objective: To determine if anterior cruciate ligament (ACL) injuries in female athletes occur randomly or correlate with a specific phase of the menstrual cycle. Design and Setting: Female athletes who sustained ACL injuries reported the days of their menstrual cycles and provided saliva samples for sex-hormone determination. Salivary sex-hormone profiles were assessed to confirm the self-reported menstrual histories. Subjects: A total of 38 female athletes (20 college, 15 high school, 1 middle school, 2 recreational) with recent ACL injuries participated in the study over a 3-year period. Measurements: Athletes with recent ACL injuries completed a questionnaire defining the injury, the last menstrual cycle, prior knee injury, school, and type of birth control used (if any). Each subject provided a 30-cc saliva sample within 72 hours of injury. Saliva samples were placed into sealed containers and frozen at −20°C. We obtained 13 additional control samples from uninjured females to test the correlation between saliva and serum sex-hormone levels. Progesterone and estrogen were assayed by radioimmunoassay. Physical examination, magnetic resonance imaging, or surgery confirmed the injury in all subjects. Results: The correlations between saliva and serum estrogen and progesterone were 0.73 (α = .01) and 0.72 (α = .01), respectively. Ten of 27 athletes who reported their cycle day at time of injury sustained an ACL injury immediately before or 1 to 2 days after the onset of menses. We rejected the null hypothesis that such high frequency was due to random chance. Conclusions: A significantly greater number of ACL injuries occurred on days 1 and 2 of the menstrual cycle. Salivary sex-hormone levels correlated with the reported cycle day.